Monophasic Synovial Sarcoma of Prostatic Fascia: Case Report and Literature Review - Lucio Olivetti; Luigi Benecchi; Serena Corti; Carlo Del Boca; Matteo Ferrari; Pietro Sergio; Luisa Bercich; Giulia Tanzi (Case Reports in Urology)
Synovial sarcoma (SS) primarily occurs in the para-articular soft tissue of the lower extremities in young adults and it is extremely rare in the prostatic region. We report a case of a 46-year-old man who presented with urinary retention. Pelvic ultrasound (US) examination, computed tomography (CT), and magnetic resonance imaging (MRI) demonstrated an 8.5 cm mass that appeared to originate in the prostatic fascia of the right lobe. Preoperative prostatic ultrasound transrectal needle biopsy revealed mesenchymal neoplastic tissue. Patient underwent surgery. The final pathologic findings were consistent with the diagnosis of monophasic synovial sarcoma.